Control of Formation of Foreign Language Written and Speech Skills with the Help of Mobile Applications: Theoretical and Methodological Model - E. K. Danilina (Научный диалог)
The issue related to the didactic system of control over the formation of foreign language competence of students on the basis of mobile applications in a non-linguistic university is considered. The purpose of the article is to describe the theoretical and methodological model of control used in teaching a foreign (English) language to undergraduate students in order to develop and improve written and speech skills. The relevance of the study is determined by the introduction of information technologies in the process of study at the university, interest in the use of mobile applications in the process of teaching a foreign language, the lack of developed methods of controlling students’ knowledge through new technologies. The article presents the author’s development of a model of evaluation of students’ written and speech skills using mobile applications. Three stages of model realization according to the developed schemes are described. The essence of the main elements of this model is revealed. The conditions necessary for successful integration of the model in the process of teaching foreign language to students in a non-linguistic university are described. The results of testing this model in the educational process are presented. It is concluded that the theoretical and methodological model proposed by the author can contribute to the optimization of the forming control system, which allows to effectively adjust the learning process.